An extra year of Onco-Nephrology fellowship training is required for the subspecialty: PRO. Issue 1 (February 2021) - Latcha, Sheron; Kala, Jaya; Kitchlu, Abhijat; Leung, Nelson
Recent advances in the fields of hematology and oncology over the past decades are truly astounding. Higher response rates have increased the overall and progression free survival, and for certain cancers, have brought the possibility of a cure within reach. While this represents great news for many cancer patients, their longer survival is creating new challenges. Cancer patients can now live long enough to develop chronic kidney disease (CKD), receive long term dialysis, and even a kidney transplantation. There are important and significant knowledge gaps in the care of the cancer patient with CKD or end stage renal disease (ESRD). The subspecialty of Onco-Nephrology was created with the goal of optimizing the care of cancer patients with CKD or ESRD by (1) identifying crucial knowledge gaps in the proper care of these patients by (2) engaging in basic science and clinical research independently and in partnership with cancer specialists to attenuate these gaps, and (3) by educating future onco-nephrologists.